Application of medicinal plants in several dermatovenerological entities - Maleš Željan; Drvar Daniela Ledić; Duka Ivan; Žužul Kristina (Acta Pharmaceutica)
Treatment of skin conditions with medicinal plants has been an ongoing human activity lasting over thousands of years. The use of specific plant species developed regionally, based on local flora. Commonly used medicinal plants for dermatological complaints are: Phlebodium aureum (L.) J. Sm., Ginkgo biloba L., Rosmarinus officinalis L., Panax ginseng C.A.Mey., Allium cepa L., Aloe vera (L.) Burm.f., Capsicum annuum L., Berbe ris aquifolium Pursh, Camellia sinensis (L.) Kuntze, and Podophyllum peltatum L.